The Valhalla Testament - Land, Jon (New York Fawcett Gold Madel, 1990)
Jamie Skylar is baffled by his sister Beth, who is living with Jose Riaz, a former Sandinista executioner; but when she begs Jamie for help, he's off to Nicaragua. When Riaz and Jamie are away for the day, assassins (apparently Contras) slaughter Beth and the rest of the household. Riaz pursues vengeance by directing a terrorist attack within the U.S.; Jamie, imprisoned by local authorities, escapes with the aid of
Keywords: Spy stories -- Terrorism